Caracterização molecular e prospecção de combinações antifúngicas sinérgicas “in vitro” frente a Trichosporon asahii, antes e após exposição prolongada ao fluconazol - Kubiça, Thaís Felli (2016)
The occurence of invasive fungal infections caused by emerging fungal pathogens has increased considerably in the last decades. The genus Trichosporon comprises species relevant in this context, due to reduced susceptibility to amphotericin B (AMB) and echinocandins, as well as the emergence of resistant strains to azole antifungals, especially to fluconazole (FCZ). Among the strategies to combat the therapeutic failures, the combination of drugs with different mechanisms of action has deserved attention. This study aimed to identify genotypically clinical isolates (n = 30), and to evaluate the susceptibility in vitro of T. asahii, before and after induction the resistance to fluconazole, to antifungal agents: AMB, FCZ, itraconazole (ITZ), voriconazole (VCZ), caspofungin (CPF), micafungin (MCF) and anidulafungin (AND), and non-antifungal compounds: tacrolimus (FK 506), diphenyl diselenide (DPDS), and ebselen (EBS), by determining the minimum inhibitory concentrations (MICs), as M27-A3 (CLSI, 2008). T. asahii was the most prevalent specie among isolates from urine and blood identified. The results MICs confirm the intrinsic resistance of T. asahii to echinocandins (MICs ≥ 4 μg mL-1), and the superiority of the triazole compounds against this specie. Moreover, it was observed that, other than AMB (MIC90 = 1 μg mL-1), the fluconazole-resistant isolates (FR) were less sensitive to azoles than fluconazole-sensitive group (FS), and this cross-resistance phenomenon is more significant forward to ITZ (90%), followed by the POS (36.67%) and VCZ (10%). The results of the antifungal associations and non-antifungal compounds against T. asahii FS and FR were evaluated by microdilution checkerboard method. FK506 (MICs > 64 μg mL-1) and the DPDS (MICs ≥ 8 μg mL-1), did not show satisfactory antifungal activity against T. asahii FS and FR. However, high percentages of synergistic interactions were exibited in the association of AMB + FK506 (96.67%), CPF + FK506 (73.33%) and AMB + DPDS (90%) against FS isolates, as well against the T. asahii FR group: CAS + DPDS (96.67%), AMB + DPDS (93.33%), FCZ + DPDS (86.67%), and ITZ + DPDS (83.33%). On the other hand, the organic compound EBS stood out by the low MIC values (0.25 to 8 μg mL-1) when tested alone, and a strong synergism in combination with AMB (90%) against T. asahii FR. Additionally, were tested combinations of AMB and echinocandins or FCZ, and CPF + FCZ against FR isolates that, other than CPF + FCZ combination (66.67% synergistic interactions), resulted in predominantly indifferent activity. Antagonistic interactions were not observed in the associations of antifungals. In this context, the in vitro exposure to increasing concentrations of fluconazole is an important factor for the emergence of resistance in T. asahii, this phenomenon brings consequences for the susceptibility profile of this specie. Moreover, the synergism observed in vitro is promising for the development of new studies to understand the activity of FK506 and organoselenium compounds against T. asahii for future application as a complementary role in the treatment of tricosporonosis.